Isolated multiple pericardial hydatid cysts in an asymptomatic patient: Role of the CMR - Bisignani, Antonio; Madeo, Andrea; Bonis, Silvana De; Vico, Riccardo; Bisignani, Giovanni (Journal of Cardiology and Cardiovascular Medicine, 2023)
Hydatid cysts primarily affect the liver and secondary involvement may be seen in almost any anatomic location. We describe the unusual pericardial location of the Echinococcus cysts in an asymptomatic patient with suggestive cardiac magnetic resonance imaging.